2017
DOI: 10.4103/0366-6999.201611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metabolic Syndrome Score, Metabolic Syndrome, and Its Individual Components on the Prevalence and Severity of Angiographic Coronary Artery Disease

Abstract: Background:The clinical significance of metabolic syndrome (MS) score, MS, and its individual components with respect to risk prediction of coronary artery disease (CAD) remains unclear. The objective of this study was to investigate whether and to what extent MS score, MS, and its individual components were related to the risk of CAD.Methods:Among 1191 participants who underwent coronary angiography for the confirmation of suspected myocardial ischemia, 858 were included in this study according to the inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…In a lipid glucose study conducted in Tehran, significant associations between BMI and various types of dyslipidemia were observed; however, WHR only maintained a significant association with hypertriglyceridemia and low HDL-C.[ 36 37 ] In China, increased BMI was found to be associated with increased TC and TG, and a negative association was ascertained between HDL and BMI. [ 38 ] We found that there were significant correlations between BMI and lipid levels (LDL-C, HDL-C, TC, and TG), and when compared with the normal weight group, as defined by BMI, the odds of dyslipidemia in the overweight and obese groups were 2.60 and 3.59 times greater, respectively.…”
Section: Discussionmentioning
confidence: 89%
“…In a lipid glucose study conducted in Tehran, significant associations between BMI and various types of dyslipidemia were observed; however, WHR only maintained a significant association with hypertriglyceridemia and low HDL-C.[ 36 37 ] In China, increased BMI was found to be associated with increased TC and TG, and a negative association was ascertained between HDL and BMI. [ 38 ] We found that there were significant correlations between BMI and lipid levels (LDL-C, HDL-C, TC, and TG), and when compared with the normal weight group, as defined by BMI, the odds of dyslipidemia in the overweight and obese groups were 2.60 and 3.59 times greater, respectively.…”
Section: Discussionmentioning
confidence: 89%
“…We previously reported that the prevalence of MetS in the United States was 33•6% in the adult population [4]. MetS predicts the development of diabetes [5] and hypertension [6], and is also associated with coronary artery disease (CAD) [7] and increased mortality [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, China is a multi-ethnic country with at least 55 ethnic groups. There are few studies focused on MetS among different ethnic groups in China, and most of these studies focused on a single ethnic group [7,12,13]. The heterogeneity in study design, inclusion criteria and definition of MetS makes it difficult to compare the prevalence in different ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] MetS is considered as a risk factor for cardiovascular disease (CVD). The presence of MetS leads to a threefold increase in CVD risk[ 2 ] and contributes to all-cause mortality. [ 3 ] The study has reported that EH was one of the key features of MetS,[ 4 ] and the presence of MetS in EH patients was higher than in the general population.…”
Section: Introductionmentioning
confidence: 99%